How Instagram Social Media Marketing Activities Shape Perceived Value, Perceived Quality, and Trust to Drive Booking Intention: A Design Thinking Case Study of Gradbyaunee in Bandung - Muhammad Amien Jauhari (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
The use of Instagram in discovery, evaluation, and initiating WhatsApp inquiries is becoming the primary way of outdoor graduation photography in Indonesia. Gradbyaunee is based in multiple cities, although Bandung performance declined in 2024-2025, which suggests a local conversion problem to the conversion process. this research is based on the Stimulus-Organism-Response framework and investigates the effect of Instagram social media marketing activities (SMMAs) on perceived value, quality, and trust and the connection of these perceptions to satisfaction and booking intention. Semi-structured interviews and prototype testing of the Bandung potential and new clients were done with the help of feasibility checks on internal operations and freelance photographers. The thematic analysis was conducted on the Instagram-WhatsApp journey, in order to determine the persistent troughs and decision points. Instagram evaluation friction is the biggest limiting factor to booking intention. The price to apparent deliverables, schedule, and procedure cannot be easily linked; the account is too spicy to be a decision guide, and trust is not always formed at a glance, while WhatsApp clearing up and Bandung-specific popularity on Instagram are not as evident. Perceived quality is the most important driver of satisfaction after the service, whereas trust and perceived value are the most important decision gates prior to making a booking. Three Instagram prototypes were created and tested, which were a pinned start here/booking flow carousels, a Bandung Spot Guide, and evidence-of-process BTS reels. Feedback We focused more on more explicit terms of commitment, better Bandung relevance, and more visible evidence to the people to increase the inquiry-to-booking conversion.